A szabadalmi jogi szerződés és hatásai a hazai jogban - Petkó, Mihály (Debreceni Jogi Műhely, 2009)
Significant changes have happened on the field of intellectual property law in the last few years. The emphasis placed on the material relations and economy became stronger. These changes caused that creations of the man came into the limelight. Of course the legal background became also very important.We can feel the re-regulation of this legal field. Legal institutions became regulated in new Acts to be adjusted modified circumstances. There were several causes of the necessity of these changes. First of all, the new economic and social environment after the change of the regime claimed to modify the legal materials. On the other hand the international environment changed rapidly and it is still in progress. So the Republic of Hungary had to face with the obligations that are stated in international treaties and we had to put a strong emphasis on our member status in the European Union: EU regulations and directives. By now we can tell that re-codifying this area is over, we can only expect to small modification in the near future.Modifications in most of the cases prepared for the future. But it does not mean that we can count on a very crystallized legal material. In the dynamically developing world of IP law it is not rare to use smaller modifications. We have to examine the legal practice too, that helps us finding the correct way in the fast changing economical and social relations. Performing the harmonization duty, legislator could not always take into consideration the national significances, legal practice. The lack of examining these circumstances can cause modifications in the legal material.The Patent Law Treaty adopted at Geneva on June 1st, 2000. The provisions of the Treaty and the Regulations shall apply to national and regional applications for patents for invention and for invention and for patents of addition, which are filed with or for the Office of a Contracting Party. The Patent Law Treaty became applicable on April 28th, 2005.Hungary joined the Treaty at the beginning, because of the need in 2008 to change the Hungarian patent law. The Treaty suggests the European Patent Convention, however in many ways it is the complementary. The Treaty gives types of applications permitted to be filed as international applications under the Patent Cooperation Treaty, divisional applications of the types of applications referred to in item.Earlier the rules of Hungarian patent law were complicated, the process of registry was less favorable for the patentee. The harmonization of process rules effects that the patentee cannot lose his patent rights. The new rules introduce an electronic process in patent law, which makes the process easier, cheaper, and faster. But not all the procedures became electronic: only the lodgment of petition. In the future that should be better to reach electronic procedure on every level.The harmonization of patent rules means liberalization, the notification will be easier and faster, which effected growth in the trust of business. Process rules need more harmonization in the future, and hopefully the final goal will be one global process at in all member states of the European Union.